Desenvolvimento de método de amostragem passiva do glifosato e seu metabólito em água - Lilian Mariane Fiuza (2021)
In recent decades, glyphosate has become the most widely used herbicide in Brazil and worldwide. In the environment, it is easily broken down by the action of microorganisms generating aminomethylphosphonic acid, whose concentration in the environment is also used as an indicator of the presence of glyphosate. Over the years, several studies have identified the negative effects of this herbicide on the health of fauna, flora, and humans, culminating in several lawsuits against the manufacturer Bayer. However, due to the physical and chemical properties of these substances, they are generally not included in routine environmental monitoring programs. Thus, the development of simple and comprehensive methods that allow the identification and quantification of glyphosate and its metabolite at low levels is extremely relevant. In this work, the efficiency of the hollow fiber supported liquid phase microextraction and hollow fiber supported solid phase microextraction techniques in the extraction of glyphosate and AMPA were evaluated with the final objective of employing them in a passive sampling device. The analytes were determined by gas chromatography coupled to a mass spectrometer and, because they have low volatility and thermal stability, a derivatization step was included prior to analysis. The derivatization procedure was optimized and the merit parameters of the method were evaluated according to the Eurachem Guide. Linearity was evaluated in the concentration range of 14 a 350 μg L-¹ and determination coefficients above 0.9 were obtained. The limits of detection and quantification obtained were 4.1 a 45 μg L-¹ and 14 a 68 μg L-¹, respectively. The intra-day and inter-day precision showed significant deviations, highlighting the need to include an internal standard for future analyses. Finally, the derivatization method was employed for analysis of water samples collected from the Marginal Lagoons of the São Francisco River.